2013
DOI: 10.1080/09205063.2013.849904
|View full text |Cite
|
Sign up to set email alerts
|

Novel gelatin/alginate soft tissue adhesives loaded with drugs for pain management: structure and properties

Abstract: Interest in tissue adhesives as alternatives for conventional wound closing applications, such as sutures and staples, has increased in the last few decades due to numerous possible advantages, including less discomfort and lower cost. Novel tissue adhesives based on gelatin, with alginate as a polymeric additive and crosslinked by carbodiimide were developed and loaded with two types of drugs for pain relief, bupivacaine and ibuprofen, in order to improve the therapeutic effect. The release of the drugs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Gelatin solutions 15% (w/v) with microbial transglutaminase have been used in vivo in a vitrectomy model (simulating retinal detachment) [137]. The bio-adhesive was seen to successfully cover a retinal tear model 7 days after administration.…”
Section: Tailoring Gelatin-based Materials To Ocular Applicationsmentioning
confidence: 99%
“…Gelatin solutions 15% (w/v) with microbial transglutaminase have been used in vivo in a vitrectomy model (simulating retinal detachment) [137]. The bio-adhesive was seen to successfully cover a retinal tear model 7 days after administration.…”
Section: Tailoring Gelatin-based Materials To Ocular Applicationsmentioning
confidence: 99%
“… 47 Overall, the study shows that this loading bupivacaine in a gelatin/ alginate bioadhesive can potentially be used for wound-closing applications. 47 …”
Section: Natural Biodegradable Polymeric Biomaterialsmentioning
confidence: 77%
“… 46 Cohen et al studied novel tissue adhesives based on gelatin, with alginate as a polymeric additive, loaded with bupivacaine or ibuprofen for pain management. 47 They found that the release of drugs from the adhesive matrix was primarily controlled by the gelatin/alginate bioadhesive’s characteristics, such as swelling and hydrophilic group concentrations that can be adjusted by changing the ratio of gelatin to alginate. 47 Moreover, they found that the hydrophilicity and electrical interactions between bupivacaine and ibuprofen with the adhesive components had some effect on the release profile of the drug, and that incorporating bupivacaine improved the bonding strength of the adhesive due to its inert nature whereas ibuprofen decreased the bonding strength due to its reactive nature with the alginate/gelatin adhesive.…”
Section: Natural Biodegradable Polymeric Biomaterialsmentioning
confidence: 99%
“…Gelatin -based tissue bioadhesives, fabricated alone or with other synthetic and natural polymers, have also been used in drug delivery. Composite tissue adhesives, developed by carbodiimide -mediated crosslinking of gelatin and alginate, were used to entrap the anti-inflammatory drugs bupivacaine and ibuprofen, and the resulting adhesive was used for local pain management [ 310 , 311 ]. Hydrophilicity of the adhesive and its swelling properties control the release of drugs from this matrix.…”
Section: Applications In Drug Deliverymentioning
confidence: 99%